Registration of 'CP 11‐1640' sugarcane. Issue 2 (5th April 2021) - Zhao, D.; Davidson, R.W.; Gordon, V.S.; Islam, Md; Sandhu, H.S.; Sood, S.; Baltazar, M.; McCord, P.H.; Migneault, A.; Coto Arbelo, O.; Momotaz, A.
Abstract: 'CP 11‐1640' (Reg. no. CV‐199, PI 695085) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by the USDA–ARS, the University of Florida, and the Florida Sugar Cane League, Inc., and released by the Florida Sugarcane Variety Committee (FSVC) to growers for commercial cultivation on mineral (sand) soils in Florida in June 2019. It was selected from a polycross made at Canal Point on 2 Jan. 2009 with Canal Point sugarcane breeding line CP 01‐2390 (female parent). Its male parent was unknown and could be any one of the clones used in the polycross. CP 11‐1640 was released by FSVC because of its high cane and sucrose yields, acceptable commercial recoverable sucrose, and resistance to brown rust, orange rust, leaf scald, Sugarcane mosaic virus strain E (mosaic), and smut. Based on the results of 12 harvests with three crops (plant cane, first ratoon, and second ratoon) at four locations in final‐stage replicated yield trials on sand soils and compared with reference cultivars (CL 88‐4730, CP 96‐1252, CPCL 97‐2730), CP 11‐1640 had significantly higher cane yield (13.4–16.9%), sucrose yield (12.0–12.8%), and economic index (10.9–16.9%) than CL 88‐4730 and CPCL 97‐2730 and did not differ from CP 96‐1252 in any of these traits. Cane fiber content of CP 11‐1640 (138.9 kg Mg −1 ) was equivalent to that of CL 88‐4730 but slightly higher than that of CP 96‐1252 and CPCL 97‐2730. CP 11‐1640 was considered to be moderately tolerant to freezing among 18 genotypes tested.